2017
DOI: 10.5455/medarh.2017.71.132-136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cigarette Smoking on Haematological Parameters in Healthy Population

Abstract: Objective:Tobacco cigarette smoking is one of the major leading causes of death throughout the world. Smoking has both acute and chronic effect on haematological parameters. The aim of the present study was to assess the extent of adverse effects of cigarette smoking on biochemical characteristics in healthy smokers.Subjects and Method:One hundred and fifty six subjects participated in this study, 56 smokers and 100 non-smokers. The smokers were regularly consuming 10-20 cigarettes per day for at least 3 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
117
5
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 167 publications
(170 citation statements)
references
References 29 publications
(29 reference statements)
18
117
5
4
Order By: Relevance
“…The significant increases in WBC count, hemoglobin, hematocrit, MCV, and MCH in those who smoked are consistent with previous studies. 7,21,22 Smith et al reported that total WBC count and its components were strongly associated with cigarette smoking and that smoking cessation may have an almost immediate impact on pathophysiologic processes such as inflammation that may be indicated by WBC count. 21 Malenica et al showed that continuous cigarette smoking had severe adverse effects on hematological parameters (eg, hemoglobin, WBC count, MCV, RBC count, hematocrit) and that these alterations might be associated with a greater risk of developing atherosclerosis, polycythemia vera, chronic obstructive pulmonary disease, and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significant increases in WBC count, hemoglobin, hematocrit, MCV, and MCH in those who smoked are consistent with previous studies. 7,21,22 Smith et al reported that total WBC count and its components were strongly associated with cigarette smoking and that smoking cessation may have an almost immediate impact on pathophysiologic processes such as inflammation that may be indicated by WBC count. 21 Malenica et al showed that continuous cigarette smoking had severe adverse effects on hematological parameters (eg, hemoglobin, WBC count, MCV, RBC count, hematocrit) and that these alterations might be associated with a greater risk of developing atherosclerosis, polycythemia vera, chronic obstructive pulmonary disease, and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…21 Malenica et al showed that continuous cigarette smoking had severe adverse effects on hematological parameters (eg, hemoglobin, WBC count, MCV, RBC count, hematocrit) and that these alterations might be associated with a greater risk of developing atherosclerosis, polycythemia vera, chronic obstructive pulmonary disease, and cardiovascular diseases. 7 Some studies have suggested that an increase in hemoglobin level in the blood of smokers could be a compensatory mechanism F I G U R E 2 The prevalence rates of obesity, smoking, and poor sleep stratified by red blood cell (RBC) count, hematocrit, mean corpuscular volume (MCV), and mean corpuscular hemoglobin (MCH). The frequencies of obesity differed among quartiles of RBC count (P < 0.0001, A); smoking, poor sleep, and obesity differed among quartiles of hematocrit (all P < 0.001, B-D); and smoking differed among quartiles of MCV and MCH (all P < 0.0001, E, F), and the trends were significantly linear (all P < 0.001) mediated by exposure to carbon monoxide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature typically shows higher levels in smokers versus non‐smokers on these parameters . The mechanism of hematological changes associated with smoking is not wholly understood, and can be a combination of multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the other studied biomarkers were either inconclusive or showed no difference based on the Bayes factors analysis. The literature typically shows higher levels in smokers versus non-smokers on these parameters [13,[35][36][37][38][39]. The mechanism of hematological changes associated with smoking is not wholly understood, and can be a combination of multiple factors.…”
Section: Discussionmentioning
confidence: 99%